THE FIVE-MINUTE-WALK DISTANCE CONCEPT, CASE STUDY: CITY OF CLUJ-NAPOCA, ROMANIA - STRINU, Oana (Studia Universitatis Babeș-Bolyai Geographia, 2019)
This term, also known as the “pedestrian shed”, refers to the distance that would make a person’s option of walking or driving to a destination differ. The distance is visualized as a 400-meter radius area most commonly found in some major cities or capitals’ downtown areas/main areas. To further highlight the characteristics of this concept I applied it on a case study of the city of Cluj-Napoca, checking the adherence of many areas against the concept’s principles. This will display the percentage of studied areas that meet the definition criteria and the results will indicate the proposed collection of measures to be adopted by the local authorities to increase the area definition validity score and to improve the citizens quality of life. This concept could be easily replicated in any city or capital and its metrics could be used to assess citizens.